Autotetraploid Origin of Chinese Cherry Revealed by Chromosomal Karyotype and In Situ Hybridization of Seedling Progenies - Yan Wang; Xueou Li; Yan Feng; Juan Wang; Jing Zhang; Zhenshan Liu; Hao Wang; Tao Chen; Wen He; Zhiwei Wu; Yuanxiu Lin; Yunting Zhang; et al. (Plants, 2023)
Polyploidy is considered a driving force in plant evolution and diversification. Chinese cherry [Cerasus pseudocerasus (Lindl.) G.Don], an economically important fruit crop native to China, has evolved at the tetraploid level, with a few pentaploid and hexaploid populations. However, its auto- or allo-polyploid origin remains unclear. To address this issue, we analyzed the ploidy levels and rDNA chromosomal distribution in self- and open-pollinated seedling progenies of tetraploid and hexaploid Chinese cherry. Genomic in situ hybridization (GISH) analysis was conducted to reveal the genomic relationships between Chinese cherry and diploid relatives from the genus Cerasus. Both self- and open-pollinated progenies of tetraploid Chinese cherry exhibited tetraploids, pentaploids, and hexaploids, with tetraploids being the most predominant. In the seedling progenies of hexaploid Chinese cherry, the majority of hexaploids and a few pentaploids were observed. A small number of aneuploids were also observed in the seedling progenies. Chromosome 1, characterized by distinct length characteristics, could be considered the representative chromosome of Chinese cherry. The basic Chinese cherry genome carried two 5S rDNA signals with similar intensity, and polyploids had the expected multiples of this copy number. The 5S rDNA sites were located at the per-centromeric regions of the short arm on chromosomes 4 and 5. Three 45S rDNA sites were detected on chr. 3, 4 and 7 in the haploid complement of Chinese cherry. Tetraploids exhibited 12 signals, while pentaploids and hexaploids showed fewer numbers than expected multiples. Based on the GISH signals, Chinese cherry demonstrated relatively close relationships with C. campanulata and C. conradinae, while being distantly related to another fruiting cherry, C. avium. In combination with the above results, our findings suggested that Chinese cherry likely originated from autotetraploidy.